PERAN TINGKAT KEMISKINAN DALAM MEMEDIASI PENGARUH UPAH MINIMUM, DAN PERTUMBUHAN EKONOMI TERHADAP INDEKS PEMBANGUNAN MANUSIA DI KABUPATEN MIMIKA - Muh. Al-Azhar Jamaluddin; Arum Santi Presilia Santoso, Winda Astika Ohoirenan (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to analyze the role of poverty levels in mediating the effects of minimum wage and economic growth on the Human Development Index (HDI) in Mimika Regency during the 2014–2023 period. Secondary data from the Central Bureau of Statistics were analyzed using a quantitative approach and path analysis method. The results indicate that the minimum wage has a positive and significant effect on HDI but is not significant in reducing poverty levels. Conversely, economic growth positively affects HDI and has a significant negative impact on poverty levels. Additionally, poverty levels do not significantly mediate the relationship between minimum wage or economic growth and HDI. The study concludes that while minimum wage and economic growth improve quality of life, their effects on poverty reduction require a more integrated approach. It is recommended that the government enhance minimum wage policies supported by economic empowerment programs and job creation to improve community welfare more effectively.